1998
DOI: 10.1149/1.1838823
|View full text |Cite
|
Sign up to set email alerts
|

14.1% CuIn1 − x Ga x Se2‐Based Photovoltaic Cells from Electrodeposited Precursors

Abstract: We have fabricated 14.1% efficient CuIn,Ga,Se2 (C1GS) based devices from electrodeposited precursors. Asdeposited precursors are Cu-rich films and are polycrystalline in nature. Additional In, Ga, and Se were added to the precursor films by physical evaporation to adjust the final composition to CuIn,_Ga,Se,. Addition of In and Ga and also selenization at high temperature are very crucial for obtaining high-efficiency devices. The X-ray analysis of the as-deposited precursor film indicates the presence of CIGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Electrodeposition of chalcogenides has emerged as an alternative low-cost method for thin film solar cell production reaching remarkable conversion efficiencies [4][5][6][7]. Most authors have used metals or metallic coated glasses as substrate for electrodeposition.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodeposition of chalcogenides has emerged as an alternative low-cost method for thin film solar cell production reaching remarkable conversion efficiencies [4][5][6][7]. Most authors have used metals or metallic coated glasses as substrate for electrodeposition.…”
Section: Introductionmentioning
confidence: 99%
“…Sputtering techniques are suitable for large-area deposition; however, they require expensive vacuum equipment and sputtering targets. Therefore, non- vacuum electrodeposition and electroless deposition (EL) techniques 10,11 with a potential to prepare large-area uniform precursor films using low-cost source materials and low-cost capital equipment are very attractive for the growth of CIGS layers for photovoltaic applications. We have fabricated 15.4%-efficient (Fig.2) and 13.4%-efficient (Fig.3) CuIn 1-x Ga x Se 2 (CIGS)-based devices from electrodeposited and electroless-deposited precursors.…”
Section: H (Tesla)mentioning
confidence: 99%
“…However, some results have shown that this could be a viable and less expensive alternative to the production of films. For instance, Bhattacharya has obtained a rich Cu-CIGSe film by electrodeposition, which was used in a photovoltaic device and has achieved an efficiency of 14.1% [10].…”
Section: Introductionmentioning
confidence: 99%